Analysis and countermeasures of large deformation of deep-buried tunnel excavated in layered rock strata:A case study. (April 2023) - Li, Jia-qi; Wang, Zhi-Feng; Wang, Ya-qiong; Chang, Hong-tao
Highlights: The main disaster-causing factors of large deformation of deep-buried tunnel in layered rock strata were identified. Large deformation mechanism of layered rock tunnels under the coupling actions of multiple factors was analyzed. The countermeasures effectively controlled the deformation of the layered surrounding rock tunnel. Optimal construction sequence of the double primary lining in the layered surrounding rock tunnel was presented. Abstract: Large deformation has been a common engineering problem during the construction of tunnels in areas with high geo-stress, the large deformation of layered surrounding rock tunnels is closed related to the rock's structural characteristics. In this paper, taking the Jiaoding tunnel as an example, large deformation of the tunnel excavated in the layered surrounding rock strata was analyzed. First, the main disaster-causing factors were analyzed through the in-situ tests, uniaxial compression tests, and immersion tests. Subsequently, the failure models of composite strata and weak interlayer were established respectively based on the geometric method and Mohr-Coulomb theory, the large deformation mechanism of layered rock tunnels under the coupling actions of multiple factors was discussed. Finally, the construction timing of the second primary lining was studied based on field tests and theoretical analysis. The results showed that the high geo-stress and special rock mass structure were the main factors leading to the large deformation of the surrounding rock. And the weak interlayers, the rheological properties of rocks, and the softening effect of groundwater on rocks were important factors that aggravate the deformation of surrounding rock. Three large deformation mechanisms of the Jiaoding tunnel were summarized: bending deformation of layered rock, deformation caused by weak interlayers, and rock rheological deformation. The second primary lining in the Jiaoding tunnel shall be constructed in time after the excavation of the middle bench, and the distance between the second primary lining and the working face of the middle bench must be less than 6 m. The research results can provide a theoretical basis and practical reference for the large deformation control of similar layered surrounding rock tunnels.